The role of Rubisco kinetics and pyrenoid morphology in shaping the CCM of haptophyte microalgae - Heureux, Ana M C (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.